THE EFFECT OF SELF-LEARNING ON WORK CULTURE - Debora, Debora (Universitas Pendidikan Indonesia, 2017)
Abstractâ The teacher is very crucial in a school with his/her competence. Especially, the teacher of tasks and roles can not be replaced even in todayâs technological era. Thus, the teacher must have a good self-learning that supports the competence and capacity as a teacher. Work culture can affect how a persons work. This work of people can not be separated from his/her capacity and competence. good working culture and ugly not be separated from onesÂ self-learning.In this study was to investigate the effect of Self-Learning teachers on Work Culture. The data were collected through participant observation using questionnaire with five options following Likertâs Scale 1-5. The participants were 74 of teachers from 7 different vocational schools in Palangka Raya city. Using testing path analysis test to indicated the effect of Self-Learning Teachersâ on Work Culture. Therefore, the self-learning teacherâs to be important to increase student skills in her/his competence and mental of character that would affect on work culture.Â Keywordsâ Â Competence; Self- Learning; lifelong learning ;Work Culture